2016
DOI: 10.4103/1305-7456.184161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bracket base design on shear bond strength to feldspathic porcelain

Abstract: Objectives:This study sought to assess the effect of bracket base design on the shear bond strength (SBS) of the bracket to feldspathic porcelain.Materials and Methods:This in vitro, experimental study was conducted on 40 porcelain-fused-to-metal restorations and four different bracket base designs were bonded to these specimens. The porcelain surfaces were etched, silanized, and bonded to brackets. Specimens were thermocycler, incubated for 24 h and were subjected to SBS. Data were analyzed using Shapiro–Wilk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Effective factors on the bond strength of brackets to enamel have been extensively discussed in several studies. They include enamel surface preparation techniques, various adhesive systems, and bracket-related factors such as area and design of the bracket base [5,6]. Recent studies have shown that 50% to 75% of patients, experience demineralization of dental surfaces during fixed orthodontic treatment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Effective factors on the bond strength of brackets to enamel have been extensively discussed in several studies. They include enamel surface preparation techniques, various adhesive systems, and bracket-related factors such as area and design of the bracket base [5,6]. Recent studies have shown that 50% to 75% of patients, experience demineralization of dental surfaces during fixed orthodontic treatment [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This review reports different ABS designs and features and shows patterns with more effective undercuts, such as laser structured and anchor pylon, which have better bond strength [ 42 , 43 , 45 , 46 ]. Also, the attachment fabrication method can influence the effectiveness of undercuts.…”
Section: Discussionmentioning
confidence: 99%
“…In the fabrication process, the Nd: YAG laser used to produce various sizes of hole-shaped undercuts caused by selectively melted metal provided micro-and macromechanical retention (Figure 5). Tis type of ABS had superior bond strength to enamel and porcelain compared with the mesh-based ones [7,[41][42][43][44]. In this type of ABS, bond failure was reported at the resinenamel interface due to maximum contact in ABS-resin interface [7].…”
Section: Laser Structuredmentioning
confidence: 99%
“…There was no statistically significant difference between American Orthodontics and Dentaurum brand brackets (Discovery metal bracket) [ 52 ]. Dalaie et al reported that the highest statistically significant bonding strength was found in Dentaurum and American Orthodontics brand metal brackets and there was no statistically significant difference between Dentaurum and American Orthodontics brand metal brackets [ 53 ].…”
Section: Discussionmentioning
confidence: 99%